Screening of microorganisms from the compost of an abandoned dumpsite for the presence of low-density polyethylene-degrading activities - Dungca, Julieta Z.; Cabrera, Esperanza C.; Paano, Anamy (2007)
Microorganisms isolated from an abandoned dumpsite (Smokey Mountain) in Manila, Philippines, were screened for the presence of low density polyethylene (LDPE)-degrading abilities. Degradation was monitored after 60 and 180 d of incubation in terms of changes in the surface morphology using scanning electron microscope (SEM), and changes in the mechanical properties using the thermal mechanical analyzer (TMA). LDPE films that showed remarkable crumple and perforations were further analyzed for changes in their thermal properties using differential scanning calorimetry (DSC) and possible functionalization of the films using Fourier transform infrared spectroscopy (FTIR). Five mixed cultures were able to degrade the LDPE films as shown in the pronounced crumple and the appearance of microcracks and perforations on the film surface compared with the control LDPE films that were not exposed to the cultures. These changes in the gross morphology were confirmed using SEM. Degradation of LDPE did not produce pronounced changes in the mechanical and thermal properties of LDPE films. Results of the FTIR did not show a new functional group but suggest a free radical mechanism. Microorganisms that were found to possess LDPE-degrading activities were identified, i. e., the bacteria Micrococcus luteus, Micrococcus varians, Bacillus cereus and Chryseomonas luteola; and the fungi Aspergillus fumigatus, Aspergillus oryzae, Penicillium and Radiomyces.
Keywords: Microorganisms; Compost; Open dumpsite